Away - Tan, Adorabelle Xiu Wen (2016)
Away is a short animated film created by Adorabelle Tan Xiu Wen and Chuang Yu Hsin, graduating Digital Animation students of 2016. Away seeks to address the problem of pollution in the world today, as well as tell a short, light-hearted story about a boy and his quest to seek nature and friendship. This report covers the processes of creating this short animated film from its pre-production, production and post-production stages, as well as a short section covering publicity material. Apart from technical aspects, the report also documents the challenges faced by the team and techniques that were developed to overcome these hurdles to create the final result.